i>Typosyllis tyrrhena (Polychaeta, Syllidae, Syllinae), a new species from the island Elba, Tyrrhenian Sea - Licherrank, F.; Kuperichael, M. (Italian Journal of Zoology (Modena, 1998)
A new Typosyllis species, T. tyrrhena (Polychaeta, Syllidae, Syllinae), from subtidal sediments off the island Elba, Tyrrhenian Sea is illustrated and described through light-microscopical and SEM investigations. T. tyrrhena sp. nov. is distinguished from other Typosyllis species by possession of (i) only a very few compound falcigerous chaetae, (ii) dorsal cirri of chaetiger 1 that are not longer and no more numerously articulated than the dorsal cirri of the following chaetigers, and (in) a very short proventricle with only a few muscular rings.
Kristian Fauchald's Polychaeta DB